PATTANI MALAY'S CULTURE AND ITS RELATIONSHIP TO EDUCATION IN SOUTH THAILAND - Mahdee Maduerawa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
The education system also aims to awaken a person in various areas of life as well as intellectual, psychological, and social thinking, values, ​​and behavior that focuses on the learning process through the good and perfect. This study aims to determine the culture of the Malay people of Pattani and the relationship with Education in southern Thailand. The research method used in this research is library research. The focal point of his research is to discover the various hypotheses, laws, recommendations, standards, or thoughts used to dissect and answer the described exam questions. The results of this study are the southern regions (provinces) of Thailand, including Yala, Pattani, and Narathiwat, where most of the population is displaced from Muslims. Muslims in this region prefer to send their children to study in religious schools. People’s religious schools are institutions that serve the needs of the community in this region in maintaining local culture and customs as well as Islamic cultural customs.